A Wearable Robotic Object Manipulation Aid for the Visually Impaired - Liu, Xiaoping; Zhang, He; Jin, Lingqiu; Ye, Cang (2018 IEEE 1st International Conference on Micro/Nano Sensors for AI, Healthcare, and Robotics (NSENS), 2018)
Due to loss of vision, it becomes a challenging task for a visually impaired individual to locate and grasp a target object. This paper presents a hand-worn assistive device that may assist a visually impaired person in detecting a target object and maintaining alignment with the object while approaching it. The device consists of a sensing module and a guiding module. The sensing module uses an RGB-D camera to detect and track the target object. The guiding module computes hand-object misalignment, determines the desired hand movement (DHM) for hand-object alignment, and uses a cable-driven exoskeleton mechanism to guide the user's hand to align with the target object. The guiding module helps to maintain hand-object alignment while the hand is approaching the object. A prototype of the device was developed and its usability was validated by experiments with human subjects.